Customer Service Recruitment Decision Support System Applying MAUT Method - Ruziana binti Mohamad Rasli; Mesran; Febrianus Gea; Setiawansyah (ADA Research Center, 2024)
Customer service is a service provided by the company to consumers who are controlled online or offline by employees of the company, either before or after purchasing products or services. Eligibility in recruitment is very important where a customer service must be able to have good and clear public speaking so that it has an impact on customers. The expected labour problem is not easy and simple, this is because the process is still manual and only based on career level, age and experience. Where, these problems also lack qualified human resources and this makes the recruitment process inaccurate and in accordance with the desired demands. So the solution is provided through a decision support system, a highly interactive computer-based system that assists in making a decision to utilise data and models in solving unstructured and semi-structured problems. In making decisions apply the MAUT method. In this research conducted using the Multi Attribute Utility Theory (MAUT) Method which is able to obtain maximum results to obtain superior recruitment personnel, namely alternative A1 with a result of 0.8975 as the top alternative after going through the method application stage.